Circuits Regulating Pleasure and Happiness: The Evolution of the Amygdalar-Hippocampal-Habenular Connectivity in Vertebrates - Loonen, Anton J. M.; Ivanova, Svetlana A. (Frontiers in Neuroscience, 2016)
Appetitive-searching (reward-seeking) and distress-avoiding (misery-fleeing) behavior are essential for all free moving animals to stay alive and to have offspring. Therefore, even the oldest ocean-dwelling animal creatures, living about 560 million years ago and human ancestors, must have been capable of generating these behaviors. The current article describes the evolution of the forebrain with special reference to the development of the misery-fleeing system. Although the earliest vertebrate ancestor already possessed a dorsal pallium, which corresponds to the human neocortex, the structure and function of the neocortex was acquired quite recently within the mammalian evolutionary line. Up to, and including, amphibians, the dorsal pallium can be considered to be an extension of the medial pallium, which later develops into the hippocampus. The ventral and lateral pallium largely go up into the corticoid part of the amygdala. The striatopallidum of these early vertebrates becomes extended amygdala, consisting of centromedial amygdala (striatum) connected with the bed nucleus of the stria terminalis (pallidum). This amygdaloid system gives output to hypothalamus and brainstem, but also a connection with the cerebral cortex exists, which in part was created after the development of the more recent cerebral neocortex. Apart from bidirectional connectivity with the hippocampal complex, this route can also be considered to be an output channel as the fornix connects the hippocampus with the medial septum, which is the most important input structure of the medial habenula. The medial habenula regulates the activity of midbrain structures adjusting the intensity of the misery-fleeing response. Within the bed nucleus of the stria terminalis the human homologue of the ancient lateral habenula-projecting globus pallidus may exist; this structure is important for the evaluation of efficacy of the reward-seeking response. The described organization offers a framework for the regulation of the stress response, including the medial habenula and the subgenual cingulate cortex, in which dysfunction may explain the major symptoms of mood and anxiety disorders.